2005
DOI: 10.1097/01.mlg.0000161339.92633.8d
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Proteases in Chronic Otitis Externa

Abstract: Elevated levels of proteases found in COE, MMP, and HNE may be inhibited with ilomastat and rAAT. The therapeutic potential of these protease inhibitors warrants investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Those proteases are involved in chronic inflammatory skin conditions such as psoriasis and atopic dermatitis as well as in inflammatory bowel diseases like Crohn's disease and ulcerative colitis (Wiedow et al, 1992;Baugh et al, 1999;Gao et al, 2005). In addition, a recent study showed elevated levels of these proteases in chronic otitis externa that could be reduced by administration of protease inhibitors (Antonelli et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Those proteases are involved in chronic inflammatory skin conditions such as psoriasis and atopic dermatitis as well as in inflammatory bowel diseases like Crohn's disease and ulcerative colitis (Wiedow et al, 1992;Baugh et al, 1999;Gao et al, 2005). In addition, a recent study showed elevated levels of these proteases in chronic otitis externa that could be reduced by administration of protease inhibitors (Antonelli et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, regarding otitis externa, we found cases of external otitis with psoriatic features have been described in 18% of patients with psoriasis, making its diagnosis complex [50]. Additionally, the frequent involvement of the ears in patients with psoriasis could imply an alteration of the epidermal barrier, which could favor superinfection by S. aureus [51]. We did find an association between middle ear infections and psoriasis based on mechanisms similar to those in cystic fibrosis.…”
Section: Comorbidity Of Psoriasismentioning
confidence: 59%